ADâLAT AL-SAHâBAH DALAM PERSPEKTIF SUNNî DAN SHî‘AH - Mahmud, Amir (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2014)
Sahâbah are narrators who occupy a prime position among other narrators of hadith chain network. In the absence of a companion is not possible news about the directions of the Prophet can come up to the next generation of Muslims. Fair (It is of râwî) nature narrator of hadith is a necessary condition that must be owned by a person who wants to tell you all about the prophet Muhammad and convey what he said. Conditions to be met, such as the hadith placed as a second source of Islam after the Koran. Unlike the case with the general history of transmitters qualifying was not so contentious. This is because the presentations of the history of society tend to be aimed at mere knowledge, is the news of the prophet in connection with religion. The emergence of groups often caused by differing views. No exception to the emergence of the Sunnî and Shî?ah, who to this day are still debating the truth claims. Then this article will discuss the background of the emergence of a group, it will provide clarity about what the objective to be achieved